Case Report: Uncommon Association of ITGB4 and KRT10 Gene Mutation in a Case of Epidermolysis Bullosa With Pyloric Atresia and Aplasia Cutis Congenita - Matyas, Melinda; Miclea, Diana; Zaharie, Gabriela (Frontiers in Genetics, 2021)
Background Epidermolysis bullosa is a rare form of genodermatosis produced by different gene mutations. The junctional form of the disease (JEB-PA) can associate pyloric atresia, renal abnormalities and aplasia cutis congenita. Case description A case of male preterm newborn with suspicion of digestive tube malformation at fetal ultrasound was born by cesarian section. At birth, he presented extensive cutaneous aplasia on the lower limbs and bilaterally under ears; outer ear agenesis; nasal septum hypoplasia; micrognathia; multiple blisters on the face, trunk and limbs; lower limb deformities and absence of toe nails. Pathological examination following a surgical procedure with unfavorable outcome showed pyloric atresia, junctional form of epidermolysis bullosa and aplasia cutis congenita. A genetic study determined that the patient carried double substitution of KRT10 and ITGB4 gene mutations, KRT10: c.1498G>T; p.Gly500* and ITGB4: c.3111+1G>A. Conclusion The particularity of our case is the novel finding that the association of two mutations in the KRT10 and ITGB4 genes can also be seen in JEB-PA.